Climate Solutions - European Investment Bank (European Investment Bank, 2019)
Climate change is the biggest threat humanity faces. So big, in fact, that it is sometimes hard to know what each of us, as individuals, can do to counter it. Climate Solutions details the challenges, lays out the solutions and shows you which ones you can make part of your life. Written by experts at the EU climate bank, each chapter helps you figure out what you can do in areas that range from how you get around to what you eat, from protecting our oceans and rivers to ensuring that your digital devices do not damage the environment.
Description based on print version record.
KU Open Services
Keywords: Science / Global Warming & Climate Change; Business & Economics / Environmental Economics; Science; Electronic books